'Roots and wings': an exploration of intergenerational play: Research. Issue 4 (2nd October 2018) - Agate, Joel R.; Agate, Sarah Taylor; Liechty, Toni; Cochran, Lynda J.
ABSTRACT: Play is an important part of life, not only during childhood but also into adulthood and later life. While scholars have emphasized the physical, social, psychological, and cognitive benefits of play for children, few researchers have explored the role of play in later life. One context in which aging adults find opportunities to play is with their grandchildren. This qualitative study employed visual and text analyses to explore the experience of intergenerational play from the perspectives of grandchildren and grandparents. Findings indicated that both groups of participants were motivated to engage in play together, negotiated constraints to experience play, and received various benefits from playing with their grandparent or grandchild. Recommendations are provided to assist professionals in programming for intergenerational play and for further exploration of the motivations, benefits, and constraints associated with intergenerational play.